Qur'anic Interpretation in the Form of Sundanese Poetry: K.H. Ahmad Dimyati's Interpretation of Q.S. al-A'lá/87 - Jajang A Rohmana (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2023)
This article examines Qur'anic interpretation in the form of Sundanese poetry, known as nadoman. The focus is on the Kitāb al Tabyīn al-Ajlá wa al-Ahlá fī Tafsīr Sūrah al-A'lá, written by K.H. Ahmad Dimyati (1886–1946). This study employs a qualitative method with a textual analysis approach, focusing on the structure, content, and context of the poetry within the Sundanese literary tradition. Data were obtained through primary analysis of the manuscript and supported by secondary literature on tafsir, Sundanese literature, and pesantren traditions. The findings show that the use of pupujian poetry in Qur'anic interpretation adds a unique dimension to the diversity of tafsir literature in West Java. While adhering to strict poetic rules, such as the nu mber of lines, syllables, and rhymes, this form of interpretation is concise, easy to memorize, and pleasant to hear. It is traditionally sung in mosques during the waiting time for prayer. However, the constraints of the poetic format limit the extent of analytical and detailed explanations, distinguishing it from conventional prose-based tafsir. This form of interpretation contributes not only to the teaching of the Qur'an but also to the preservation and development of Sundanese literary tradition, highlighting the integration of religious education with local culture. This study provides a significant contribution to Islamic scholarship by bridging Qur'anic interpretation with local literary traditions, demonstrating how poetry can serve as an effective medium for transmitting religious teachings. Methodologically, the study underscores the importance of combining textual and cultural analysis to explore localized forms of Qur'anic studies.